Isobaric tags for relative and absolute quantification-based proteomic analysis of host-pathogen protein interactions in the midgut of Aedes albopictus during dengue virus infection - Wang, Jiatian; Fan, Peiyang; Wei, Yong; Wang, Jiaqi; Zou, Weihao; Zhou, Guofa; Zhong, Daibin; Zheng, Xueli (Frontiers in Microbiology, 2022)
Aedes albopictus (Ae. albopictus), an important vector of dengue virus (DENV), is distributed worldwide. Identifying host proteins involved in flavivirus replication in Ae. albopictus and determining their natural antiviral mechanisms are critical to control virus transmission. Revealing the key proteins related to virus replication and exploring the host-pathogen interaction are of great significance in finding new pathways of the natural immune response in Ae. albopictus. Isobaric tags for relative and absolute quantification (iTRAQ) was used to perform a comparative proteomic analysis between the midgut of Ae. albopictus infected with DENV and the control. 3,419 proteins were detected, of which 162 were 1.2-fold differentially upregulated or 0.8-fold differentially downregulated (p < 0.05) during DENV infections. Differentially expressed proteins (DEPs) were mainly enriched in ubiquitin ligase complex, structural constituent of cuticle, carbohydrate metabolism, and lipid metabolism pathways. We found that one of the DEPs, a putative pupal cuticle (PC) protein could inhibit the replication of DENV and interact with the DENV-E protein. In addition, the result of immunofluorescence test showed that there was co-localization between ubiquitin carboxyl-terminal hydrolase (UCH) protein and the DENV-E protein, and virus infection reduced the level of this protein. iTRAQ-based proteomic analysis of the Ae. albopictus midgut identified dengue infection-induced upregulated and downregulated proteins. The interaction between the PC and UCH proteins in the midgut of Ae. albopictus might exert a natural antiviral mechanism in mosquito.